Experimental measurement on the viscosity of supercritical carbon dioxide. (February 2020) - Zhou, Yi; Ni, Hongjian; Shen, Zhonghou; Liu, Weili
Highlights: A visual experimental system was designed to measure the viscosity of SC-CO2 . The viscosity of SC-CO2 was measured based on particle settling method. A power-law correlation between Archimedes and Reynolds numbers was obtained. The correlation can be used to measure viscosity with a scope of 1000 <  Re  < 25000. The viscosity error measured by this method is basically within 10%. Abstract: In this paper, a generalized and pragmatic experimental method has been established to measure the viscosity of SC-CO2 which can be used to estimate SC-CO2 tackifier in the application of CO2 . A visualization apparatus and high-speed camera system were used to record the settling process and the terminal velocity of particles were measured. The terminal velocity tests in SC-CO2 are conducted to examine the effect of pressure, temperature, particle size and particle type under different conditions of various pressures (6–16 MPa), temperatures (35–70 °C) and different particles (Steel, Glass, Aluminum). A power-law relationship between the particle's Reynolds (Reynolds number range: 1000–25000) and Archimedes numbers was found due to the experimental results. Using the power-law relationship, viscosity of SC-CO2 can be easily calculated according to the terminal of particle measured in the experiment.